Embracing nature: Ecocritical insights into the harmonious world of Ezra Pound’s The Canto XLIX - Shang, Jingmei; Mohsen, Hamoud Yahya Ahmed; Jijun, Wang; Hongmei, Zhang; Li, Xu (UPSI Press, 2025)
This study is aimed to explore the harmonious world of Ezra Pound’s poetry with special reference to his notorious long poem deprived from the version of The Cantos of Ezra Pound (1975), the Canto XLIX, which is part of The Fifth Decad of Cantos (1937). The authors employ the recent theory of ecocriticism as a reading lens in the current study engaging three key ecocritical concepts, namely, the harmony with nature, nature as a symbol and the unity with nature. Through a close ecocritical reading the simple but beautiful verses of the long poem, the authors find a strong ecological concern and involvement of the human and natural worlds. The analysis of the selected poem reveals that Pound conceived a great deal of conception and thought on the description of ecological vision, including the harmonious unity of human and nature throughout the poem. On the one hand, the vision of his writing is ecologically rich, as reflected in his realistic living environment and the poem’s depiction of nature. On the other hand, the expression of the poem is sensual, as displayed in the poet’s poetic creation incorporating the idea of at one with nature, which evokes to a certain extent the contemporary sensitivity to ecological concerns for the environment, and even the current social and environmental challenges, as well as the nature-literature connection that is increasingly evident in literary studies. The poet’s depiction of the natural environment inspires a deep sense of at one with nature, which can be seen as underlying ecological concern